Hydrothermal synthesis of lanthanide‐doped GdPO4 nanowires and nanoparticles for optical applications. Issue 2 (28th January 2014) - Hernández, A. Garrido; Boyer, D.; Potdevin, A.; Chadeyron, G.; Murillo, A. García; de J. Carrillo Romo, F.; Mahiou, R.
<x xml:space="preserve">Abstract</x> In this work, Eu3+ and Tb3+ doped GdPO4 nanocrystals, with different shapes were successfully synthetized by an original hydrothermal method. The particles morphology was modified changing the pH value and using glycerol as co‐solvent in the synthesis. Depending on the synthesis conditions, TEM analyses have revealed the achievements of nanowires and nanoparticles with narrow size distributions. Their structural, morphological, and photoluminescent properties were investigated and compared. Luminescent composite films based on silicone polymer were prepared using GdPO4:Eu3+ and GdPO4:Tb3+ with different morphology as filler. <inline-graphic xlink:href="ark:/27927/pgg4swd4jv7" content-type="pssa201300214-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />